THE RELATIONSHIP BETWEEN PHILOSOPHY AND ARCHITECTURE: THE INTERACTION BETWEEN THOUGHTS AND FORMS OF LIVING SPACE (Isagoge - Journal of Humanities and Social Sciences, 2025)
This paper delves into the mutual relationship between philosophy and architecture, emphasizing the role of philosophy as a foundation for architectural thinking, and how architecture exhibits feedback, exerting a reciprocal influence on philosophy. Through examples from historical to contemporary architecture, the paper clarifies the interplay between abstract theories and spatial forms and draws out methodological implications for both fields. The aim is to provide a comprehensive and insightful view of this dialectical relationship in the context of social development and architectural trends.
Keywords: Philosophy, architecture, space, thoughts, methodology, two-way interaction